2003
DOI: 10.14214/sf.483
|View full text |Cite
|
Sign up to set email alerts
|

Addition of stabilized wood ashes to Swedish coniferous stands on mineral soils - effects on stem growth and needle nutrient concentrations

Abstract: Increasing use of forest fuels for energy production is generating increasing quantities of wood ash. A common understanding is that this ash should be spread in forests to counteract soil acidifi cation and potential future nutrient defi ciencies, and thus help sustain longterm forest productivity. A series of seven fi eld experiments was established in Sweden in 1988-1995 to study the stem growth and needle nutrient concentrations of 30-60-year-old Scots pine (Pinus sylvestris L.) and Norway spruce (Picea ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 22 publications
10
107
2
4
Order By: Relevance
“…Usually ash fertilization does not improve tree stand production on mineral soil forests (Jacobson 2003, Saarsalmi et al 2004, probably because on those nitrogen and not K or P limits tree growth. However, on peat soils K and P deficiency is common and may limit tree growth (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Usually ash fertilization does not improve tree stand production on mineral soil forests (Jacobson 2003, Saarsalmi et al 2004, probably because on those nitrogen and not K or P limits tree growth. However, on peat soils K and P deficiency is common and may limit tree growth (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Strudley et al [11], observed that tillage methods and intensity have various effects on the soil physical and chemical properties that affect plant growth and crop yield. Also wood ash have been reported by Vuorinen and Kurkala [12] and Jacobson [13] to have positive effect on Ca, K, content of soil as well as an increase of K, Mg, S, B, Fe and Zn in tissue of the Scots Pine.…”
Section: /19mentioning
confidence: 95%
“…Though wood ash amendment in mineral soils was found not to have any positive growth response in plants growing on such soils [13] [15]. Enriching the soil with wood ash would cause some changes in the metabolism and physiological activity of plants [14] [16] and soil properties.…”
Section: /19mentioning
confidence: 99%
“…Guerrini et al (2000) found that wood ash and paper sludge applications on predominantly sandy soils can increase growth in the range of 38% to 64% relative to chemical fertilizers. The addition of a supplementary nitrogen-rich nutrient source has been shown to increase growth and is recommended if improved growth responses are anticipated from wood ash additions (Demeyer et al 2001, Jacobson 2003, Elliott & Mahmood 2006.…”
Section: Growth Responsementioning
confidence: 99%